Low-intensity elbow flexion eccentric contractions attenuate maximal eccentric exercise-induced muscle damage of the contralateral arm. Issue 10 (October 2018) - Chen, Trevor C.; Lin, Ming-Ju; Lai, Jian-Han; Chen, Hsin-Lian; Yu, Hui-I; Nosaka, Kazunori
Abstract: Objectives: The magnitude of muscle damage induced by maximal eccentric contractions (MaxEC) of the elbow flexors (EF) is reduced when it is preceded by low-intensity (10% of maximal voluntary isometric contraction strength) eccentric contractions (10%EC) of the same muscle, or by MaxEC of the opposite EF. This study investigated whether 10%EC would reduce the magnitude of muscle damage after MaxEC performed by the opposite arm. Design: Comparison among 6 groups for changes in indirect markers of muscle damage. Method: Young (21.0 ± 1.8 years) untrained men were assigned to five experimental groups (n = 13/group) that performed 30, 10%EC followed by 30 MaxEC of the other arm performed at either 1 (1d), 2 (2d), 7 (1wk), 14 (2wk) or 21 days (3wk) later, and one control group that performed 30 MaxEC without 10%EC (n = 13). Changes in several indirect markers of muscle damage after MaxEC were compared among the groups by mixed-design two-way ANOVAs. Results: No significant changes in maximal voluntary concentric contraction torque, plasma creatine kinase activity and muscle soreness were evident after 10%EC. Changes in these variables after MaxEC were smaller (p < 0.05) for the 1d, 2d and 1wk groups than control group, without significant differences between the 1d, 2d and 1wk groups. No significance differences in the changes were evident among the 2wk, 3wk and control groups, except for muscle soreness showing smaller (p < 0.05) increases for the 2wk and 3wk groups than control group. Conclusions: These results showed that 10%EC conferred muscle damage protection to the contralateral arm that performed MaxEC.